2010
DOI: 10.1007/s10661-010-1458-8
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and bioavailability of phosphorus in a tropical estuary, Southwest India

Abstract: Phosphorus fractionation was employed to find the bioavailability of phosphorus and its seasonal variations in the Panangad region of Cochin estuary, the largest estuarine system in the southwest coast of India. Sequential extraction of the surficial sediments using chelating agents was taken as a tool for this. Phosphate in the water column showed seasonal variations, with high values during the monsoon months, suggesting external runoff. Sediment texture was found to be the main factor influencing the spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Although P-Ca was more stable than P-Fe, this fraction was significantly regulated by pH and the carbonate content (Ren et al 2012; Wang 2012; Gireeshkumar et al 2013; Zhang et al 2015). A study on the fractionation and bioavailability of phosphorus in a tropical estuary in southwestern India indicated that high concentrations of P-Ca might be interpreted as the result of the accumulation of calcium in estuarine environments under favorable higher salinity and pH conditions (Renjith et al 2011). The same study indicated that salinity controls the flocculation and sedimentation mechanisms in estuarine environments.…”
Section: Resultsmentioning
confidence: 99%
“…Although P-Ca was more stable than P-Fe, this fraction was significantly regulated by pH and the carbonate content (Ren et al 2012; Wang 2012; Gireeshkumar et al 2013; Zhang et al 2015). A study on the fractionation and bioavailability of phosphorus in a tropical estuary in southwestern India indicated that high concentrations of P-Ca might be interpreted as the result of the accumulation of calcium in estuarine environments under favorable higher salinity and pH conditions (Renjith et al 2011). The same study indicated that salinity controls the flocculation and sedimentation mechanisms in estuarine environments.…”
Section: Resultsmentioning
confidence: 99%
“…In Akaipur, they were as high as 9490 mg kg ¡1 and up to 11,700 mg kg ¡1 in the rainy season (selected from the full data set preaveraging). These were much higher than those reported by others (Banerjea and Ghosh, 1970;Rzepecki, 2010;Renjith et al, 2011). The average sediment C:P ratios were also low (C:P D 5.39, 6.79 by mass for Akaipur and Bhomra, respectively) indicating P enrichment.…”
Section: Discussionmentioning
confidence: 51%
“…Aluminum bound P is stable and less mobile than iron bound P (Ann et al, 2000). Phosphorus fractionation gives valuable information about potential internal loading or fixation of P in sediment and is a useful tool in long-term trophic state management of lakes and rivers (Psenner et al, 1984;Renjith et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, large amounts of shellfish live in southern lake, where apatite can be formed at the surface of shell fragments (Tab. ) . Fe/Al–P had a large spatial variation, with higher concentrations at NW corner and the western tip where external pollution from the discharge of wastewater is serious.…”
Section: Discussionmentioning
confidence: 99%